Lessons Learned from Thomas Modly's Strategic Leadership in Enhancing United States Maritime Security: Indonesia - Muhamad, Faisal; Soemantri, Asep Iwa; Prakoso, Lukman Yudho; Suwarno, Panji; Ruslinar, Meli; Zahra, Raesha Syahnaz; Triyani, Triyani; Oktaviandra, Yosyea; Novitasari, Yussie (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This article explores lessons learned from Thomas Modly's leadership in improving U.S. maritime security, through various approaches such as system and ship modernization, cybersecurity, international partnerships with countries directly related to U.S. maritime interests, and operational readiness through repair, maintenance and logistics to improve efficiency and effectiveness. This study also evaluates the relevance of these steps to improving maritime security in other countries, especially countries with large sea areas. In addition, this study also offers an effective model in addressing maritime security challenges from various contexts.